Home grocery delivery improves the household food environments of behavioral weight loss participants: Results of an 8-week pilot study - Niemeier Heather M; Raynor Hollie A; Gorin Amy A; Wing Rena R (BMC, 2007)
Abstract Background Household food availability is consistently linked to dietary intake; yet behavioral weight control treatment includes only minimal instruction on how to change the home environment to support dietary goals. This pilot study examined whether it is feasible to change the household food environments of behavioral weight loss participants through the use of a commercially available grocery home delivery service. Methods Overweight participants (N = 28; BMI = 31.7 ± 3.6 kg/m2; 89.3% women, 47.9 ± 9.5 years) were randomly assigned to 8-weeks of standard behavioral weight loss (SBT) or to SBT plus home food delivery (SBT+Home). SBT+Home participants were instructed to do their household grocery shopping via an online service affiliated with a regional supermarket chain and were reimbursed for delivery charges. Results Compared to SBT, SBT+Home produced significantly greater reductions in the total number of foods in the home (p = .01) and number of foods that were high in fat (p = .002). While the groups did not differ in 8-week weight losses, within SBT+Home there was a trend for the number of home deliveries to be associated with weight loss (p = .08). Participants reported that the home delivery service was easy to use and that it helped decrease impulse purchases and lead to healthier choices; however, few planned to continue using the service after the study. Conclusion Encouraging weight loss participants to use a commercially available online grocery ordering and home delivery service reduces the overall number of food items in the home and decreases access to high-fat food choices. More research is needed to determine whether this is a viable strategy to strengthen stimulus control and improve weight loss outcomes.